METAIS PESADOS EM SEDIMENTOS SUPERFICIAIS DA LAGOA MIRIM, FRONTEIRA BRASIL-URUGUAI - Santos, Isaac Rodrigues dos; Baisch, Paulo; Lima, Guilherme Theodoro Nascimento Pereira de; Silva-Filho, Emmanoel Vieira da (Geochimica Brasiliensis, 2011)